2019
DOI: 10.2174/1875318301909010084
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vascular Endothelial Growth Factor in Patients with Hepatocellular Carcinoma and its Validity as a Tumor Biomarker

Abstract: Background: Hepatocellular Carcinoma (HCC) is one of the most common cancers associated with deaths worldwide and the presence of valid biomarkers for early diagnosis in high-risk patients can ameliorate the outcome of HCC. Vascular Endothelial Growth Factor (VEGF) has been found to play an essential role in the process of HCC growth and progression. Objectives: Therefore, we evaluated the serum VEGF levels in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…Immunohistochemical (IHC) studies have shown that VEGF expression is not confined to the tumor area but also in surrounding non-tumor areas in a similar manner 26 , 27 . Concordant with these findings, there was no significant difference in the median serum VEGF levels between HCC patients and cirrhotic patients without HCC 28 . In contrast, Ang2 has been observed to be more highly expressed in tumor tissues than in surrounding non-tumor tissues and to be less expressed in the normal liver 29 .…”
Section: Discussionsupporting
confidence: 78%
“…Immunohistochemical (IHC) studies have shown that VEGF expression is not confined to the tumor area but also in surrounding non-tumor areas in a similar manner 26 , 27 . Concordant with these findings, there was no significant difference in the median serum VEGF levels between HCC patients and cirrhotic patients without HCC 28 . In contrast, Ang2 has been observed to be more highly expressed in tumor tissues than in surrounding non-tumor tissues and to be less expressed in the normal liver 29 .…”
Section: Discussionsupporting
confidence: 78%